A simple and reliable pretreatment protocol facilitates fluorescent in situ hybridisation on tissue microarrays of paraffin wax embedded tumour samples. Issue 5 (26th September 2003) - Chin, S-F; Daigo, Y; Huang, H-E; Iyer, N G; Callagy, G; Kranjac, T; Gonzalez, M; Sangan, T; Earl, H; Caldas, C
Abstract : Aims: To describe a robust pretreatment protocol for preparing paraffin wax embedded tissues on tissue microarrays for fluorescence in situ hybridisation (FISH). The newly developed pretreatment protocol described here was compared with the commonly used sodium thiocyanate based protocol and two different heating methods used in standard antigen unmasking protocols for immunohistochemistry (pressure cooking and microwaving in citrate acid buffer). Methods: Dewaxed tissue sections were incubated in 10mM citric acid buffer at 80°C for 30 minutes to two hours, followed by a short pepsin digestion (1–5 mg/ml). Pretreated tissues were co-denatured with DNA probes at 80°C for 10 minutes, followed by hybridisation at 37°C for 48–72 hours. Results: The three protocols using citrate acid buffer produced FISH signals with superior signal to noise ratios compared with sodium thiocyanate pretreatment. Most importantly, the best tissue attachment was achieved using the newly developed pretreatment protocol: on tissue microarrays less than 1% of cores were lost. To date, a total of 30 probes have been successfully hybridised on to breast tissue and multi-tissue microarrays. Conclusion: This pretreatment protocol is easy, reproducible, and facilitates FISH on tissue microarrays, with potential for widespread application in cancer research.